Adsorption of Nitrate Ions Using Magnesium-Loaded Bamboo Powder and Nano-Sized Crushed Oyster Shells - Harada Hiroyuki; Nur Maisarah Mohamad Sarbani; Aoyagi Misturu; Jun Nishimoto (Separations)
Excess nitrate ions should be avoided in agriculture as they are absorbed by plants and ingested by humans, which can have serious effects on soil and groundwater. In this study, environmentally friendly bamboo flour and nano-sized oyster shells were used as adsorbents. The equilibrium time for nitrate adsorption was found to be short, less than five minutes, and the treatment temperature had little effect on adsorption. The adsorption capacity and adsorption mechanism were investigated using experiments and adsorption isotherms. Bamboo powder treated with magnesium chloride (Mg bamboo), crushed oyster shell (oyster shell), and hydrogel induced with sodium alginate (hydrogel) were used. The maximum adsorption of nitrate ions on the magnesium-treated bamboo flour was estimated to be 399 mg NO3−/g by the Dubin–Radushakevich equation (correlation coefficient 0.84), with the Langmuir (correlation coefficient 0.91) and Freundlich (correlation coefficient 0.91) equations also fitting relatively well. The D-R equation (correlation coefficient 0.938) and Freundlich equation (correlation coefficient 0.943) also fitted oyster shells relatively well. The maximum adsorption was estimated at 354 mg NO3−/g. In oyster shell treatments where phosphate and nitrate ions were present, it was observed that both substances were adsorbed simultaneously. For the hydrogels, only the D-R equation (correlation coefficient 0.944) and the Freundlich isotherm were applicable. The maximum adsorption was estimated at 156 mg/g.